What Lies Under the White Lights: A Screenplay Exploring the Effects of Post-TruthFound in False Allegations Online Using the Crime Genre - Andrew Nathanael Tanojo; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2026)
Post-Truth can be easily observed manifesting in the current era in various forms. False allegations serve as one form of this theory taking place, one which impact can be prominently seen today. This creative work, a screenplay of the crime genre, discusses this by using it as an ever present dread present in multiple aspects of the story. Alexander Nugraha is faced with a false allegations case rooted in Post-Truth, where he is constantly thwarted with other forms of Post-Truth in his city. It hinders his success in figuring out the case until he is forced to realize his reality and starts to see the world for what it is, full of Post-Truth and falsehoods. With this realization, Alexander is able to figure out the right path, solve the case, and defeat the Post-Truth problem in front of him.